THE INCOME TAX–DEPLETION AND DEPRECIATION. - Grimes, J. A. (The Accounting Review, 1928)
The ratification of the constitutional amendment permitting the taxation of income became effective on March 1, 1913 in the U.S. Therefore, appreciation in value after that date is subject to an income tax, but appreciation to March 1, 1913, is tax-free. This feature required the valuation of property of all kinds as at one specific time. Depletion and depreciation deductions from taxable income are merely provisions for the return of value when properties are consumed in the process of production, and are thus sold piecemeal to the purchaser of marketable products. Valuations have also been required as at date of acquisition in determinations of invested capital for excess profits tax purposes; and current valuations, year by year, have been necessary for the capital stock tax assessments. The estate tax also necessitates valuation, in some instances numerous valuations of the same property at various dates. Further, many facilities were acquired strictly for war purposes, and the difference between the cost of such facilities and their value for post-war use was recognized by Congress as a fair deduction from war-time income.